2008
DOI: 10.1175/2007jcli1584.1
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic Circulation and Land Surface Influences on Convection in the Midwest U.S. “Corn Belt” during the Summers of 1999 and 2000. Part II: Role of Vegetation Boundaries

Abstract: In Part I of this observational study inquiring into the relative influences of "top down" synoptic atmospheric conditions and "bottom up" land surface mesoscale conditions in deep convection for the humid lowlands of the Midwest U.S. Central Corn Belt (CCB), the composite atmospheric environments for afternoon and evening periods of convection (CV) versus no convection (NC) were determined for two recent summers (1999 and 2000) having contrasting precipitation patterns and amounts. A close spatial correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 88 publications
3
18
0
Order By: Relevance
“…Our results here indicate that the convective schemes used in GCMs might also be part of the reason. Berg et al [2013] also attributed the difference of TFS results and those in other studies showing negative feedbacks [e.g., Carleton et al, 2008;Wang et al, 2009;Taylor et al, 2011Taylor et al, , 2012 to the coupling indices framework and the spatial scale difference. The positive feedback as shown through TFS in our coarse spatial resolution simulations ($2.88 here) is not necessarily contradictory with those studies that emphasize scales of coupling in the 10-100 km range accounting for surface heterogeneity, which are not included in our framework.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 82%
“…Our results here indicate that the convective schemes used in GCMs might also be part of the reason. Berg et al [2013] also attributed the difference of TFS results and those in other studies showing negative feedbacks [e.g., Carleton et al, 2008;Wang et al, 2009;Taylor et al, 2011Taylor et al, , 2012 to the coupling indices framework and the spatial scale difference. The positive feedback as shown through TFS in our coarse spatial resolution simulations ($2.88 here) is not necessarily contradictory with those studies that emphasize scales of coupling in the 10-100 km range accounting for surface heterogeneity, which are not included in our framework.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 82%
“…Such studies indicate that, on scales of 10-100 km, sharp gradients in surface fluxes induced by soil moisture or vegetation patterns may generate daytime mesoscale circulations (analogous to sea breezes), resulting in enhanced convergence and convection over warm surface anomalies. For instance, studies based on remote sensing data have shown that in regions as varied as West Africa (Taylor et al 2011), the Amazon (Wang et al 2009), or the Midwest (Carleton et al 2008), convection may be favored over drier areas in the presence of such surface heterogeneity. Most recently, using recent global high-resolution (0.258) satellite retrievals of soil moisture and precipitation, Taylor et al (2012) have shown a globally consistent negative feedback in which afternoon precipitation occurs preferentially over soils that are relatively dry compared to the surrounding area, with the strongest signal emerging in semiarid regions.…”
Section: Discussion: Assessing the Evaporationprecipitation Feedbackmentioning
confidence: 99%
“…Here, we report on energy balance measurements over a new exurban residential area near Kansas City, Missouri during an intensive observation period in August 2004. This study is part of a larger programme to improve the representation of urban and rural land-use transitions in regional climate models (Adegoke et al 2007;Carleton et al 2008). The primary goal of the intensive field study was to determine whether the surface energy partition in the rapidly growing exurban residential land-use types could be parameterized in regional climate models similarly to the suburban surface types for which values are known from previous field campaigns in diverse urban regions.…”
Section: Introductionmentioning
confidence: 99%